Non-Small Cell Lung Cancer with Chest Wall Involvement: Integrated Treatment or Surgery Alone? - Chiappetta, Marco; Nachira, Dania; Congedo, Maria Teresa; Meacci, Elisa; Porziella, Venanzio; Margaritora, Stefano (The Thoracic and Cardiovascular Surgeon, 2019)
Background The aim of this study was to identify prognostic factors in patients affected by non-small cell lung cancer (NSCLC) with chest wall (CW) involvement, analyzing different strategies of treatment and surgical approaches.Methods Records of 59 patients affected by NSCLC with CW involvement underwent surgery were retrospectively reviewed, from January 2000 to March 2013.Results Induction therapy was administered to 18 (30.5%) patients while adjuvant treatment to 36 (61.0%). In 36 (61%) patients, lung resection was associated only with a parietal pleural resection while in 23 (39%) with CW en-bloc resection. Overall 5-year survival was 34%. Prognostic factors were evaluated in the 51 (86.4%) completely resected (R0) patients.Five-year survival was 60% in patients undergoing induction therapy followed by surgery and 24% in those who underwent surgery as first treatment (p = 0.11). Five-year survival was better in the neoadjuvant group than that in the surgery group in IIB (T3N0) p-stage (100 vs 28%, p = 0.03), while in the IIIA (T3N1–2,T4N0) p-stage it was of 25 vs 0%, respectively (p = 0.53).No 5-year survival difference was found in case of parietal pleural resection versus CW en-bloc resection (p = 0.27) and in case of only parietal pleural involvement versus soft tissue (p = 0.78).In case of incomplete resection (R1), patients undergoing adjuvant radiotherapy had better 2-year survival than patients untreated: 60% vs 0% (p = 0.025).Conclusions Type of surgical resection and the deep of infiltration of disease do not influence survival in this subset of patients. Integrated treatments seem to be suitable: neoadjuvant therapies ensure a better survival rate than surgery alone in IIB and IIIA patients, instead adjuvant radiotherapy proves a fundamental option in incomplete resections.
Keywords: lung cancer surgery; chest wall; surgery/incisions/exposure/techniques; neoadjuvant induction therapy; radiation therapy